Improving Students’ Writing Short Story Skill through Time Token Learning and Video Media - Raditya Ranabumi; Muhammad Rohmadi; Slamet Subiyantoro (Intelektual Pustaka Media Utama, 2017)
This research is a class action research aiming to develop the short story writing skill score in grade VII C students of SMPN 5 Kediri academic year 2016/2017. The result of this study showed that there was an increasing in the mean score of students' short story writing skills through the Time Token learning model and video media. In the first cycle, the percentage of students’ completion was 33.3% with an mean score of 73.4. Then in cycle II the percentage of students’ completeness was 62.3% with an mean score of 76.6. Furthermore, it can be concluded that the use of Time Token learning model and video media can increase the score of the learning achievement of short story writing skills of VII C grade SMPN 5 Kediri students in the academic year 2016/2017.